Combination of tadalafil and finasteride for improving the symptoms of benign prostatic hyperplasia: critical appraisal and patient focus - Elkelany OO; Owen RC; Kim ED (Dove Medical Press, 2015)
Osama O Elkelany, Ryan C Owen, Edward D KimDepartment of Surgery, Division of Urology, University of Tennessee Graduate School of Medicine, Knoxville, TN, USAAbstract: The evidence suggests that combination therapy for benign prostatic hyperplasia (BPH)-lower urinary tract symptoms (LUTS) using an α-blocker and a 5α-reductase inhibitor has become well accepted. The combination of daily tadalafil and an α-blocker has also demonstrated benefit. This paper addresses combination therapy with daily tadalafil and finasteride for the treatment of BPH-LUTS. Our results demonstrate that use of tadalafil and finasteride represents a logical extension of combination therapies. We analyze a landmark study by Casabé et al that demonstrates improved voiding symptoms as assessed by International Prostate Symptom Scores with a combination of tadalafil and finasteride compared with finasteride and placebo. Study patients had moderate to severe LUTS and prostate volumes >30 g. The additional benefit of improved erectile function as assessed by International Index of Erectile Function-erectile function domain scores with the addition of tadalafil was a secondary benefit. We propose that the ideal patient for combination therapy with tadalafil and finasteride has a prostate volume >30 g and desires additional benefit over monotherapy. For these men, improved erectile function without sexual side effects was a secondary benefit.Keywords: benign prostatic hyperplasia, lower urinary tract symptoms, tadalafil, finasteride